2018
DOI: 10.1111/nep.13113
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcification score and common iliac artery calcification score in non‐dialysis CKD patients

Abstract: Summary at a GlanceVascular calcification is a major contributor to morbidity and mortality in patients with CKD, although the optimal method and site for measurement of vascular calcification have not been determined. This study assesses and compares coronary artery calcification and common iliac artery calcification determined by CT in a cohort of non‐dialysis CKD patients and reports on associated variables and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Vascular calcification is a critical complication in patients with CKD. Calcification of arterioles within the endothelial and medial layers induces arterial stiffness and occlusion, which may cause coronary artery disease and calciphylaxis in peripheral vessels [2,3,4]. Therefore, vascular calcification is predictive of poor prognoses and clinical outcomes in CKD patients, such as overall mortality and even poor arteriovenous graft maturation [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular calcification is a critical complication in patients with CKD. Calcification of arterioles within the endothelial and medial layers induces arterial stiffness and occlusion, which may cause coronary artery disease and calciphylaxis in peripheral vessels [2,3,4]. Therefore, vascular calcification is predictive of poor prognoses and clinical outcomes in CKD patients, such as overall mortality and even poor arteriovenous graft maturation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous basic studies showed that the rate of ostelcalcin and MGP secretion increased after treatment with vitamin D. Fraser et al first noticed that the protein and mRNA expression of MGP in osteosarcoma cell line increased after 1.25(OH)2D treatment at the concentration of 0.3 nM for more than 48 h. They also found vitamin D can stimulate osteocalcin synthesis earlier and at lower vitamin D levels compared to MGP production. [3]. In osteoblasts, 1.25(OH)2D increases vitamin K-dependent binding protein-related osteocalcin expression, which could maintain the mineralization of osteoblasts into osteocytes [72,73].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the relatively small sample sizes of participants with CKD stage 1 and 5 ND may attenuate the association between kidney function and calcium scores. Moreover, reported patterns of independent risk factors for calcification differ with arterial sites in both CKD cohorts [27,36] and the general population [28,37,38]. Most likely, the inconsistent patterns reflect differences in the studied populations as well as different methods for registration of risk factors and diverging sensitivity of CT scanning protocols.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies applying CT scans have assessed calcification beyond the coronary arteries. Mizuiri et al [27] reported calcification in both the coronary (81.4%) and iliac arteries (87.4%) in 145 individuals with a median age of 72 years, a median eGFR of 32 mL/min/1.73 m 2 and a high prevalence of diabetes and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular calcification, which involves the deposition of calcifying particles within the endothelial layer or smooth muscle within the medial layer, is an important issue due to its associated complications, such as peripheral arterial occlusive disease and coronary artery disease [1][2][3]. Several conditions, including insulin resistance, hypertension, acute decompensated heart failure, chronic kidney disease (CKD), dyslipidemia, vitamin D deficiency, and metabolic syndrome, are associated with vascular calcification [4][5][6].…”
Section: Introductionmentioning
confidence: 99%